ANALYSIS OF OMISSION ERRORS IN CHINESE CONVERSATIONAL SENTENCES AMONG THAI COLLEGE STUDENTS - Huang, Mingwei; Funoi, Pawares (Chinese Language and Culture Journal, 2024)
This study utilizes a theoretical framework of second language acquisition and error analysis to investigate 1,500 spoken Chinese sentences from the assignments of 79 Thai sophomore students. The errors can be broadly classified into seven categories: omissions, redundancies, unsuitable vocabulary, inappropriate punctuation, typos, word order, and mixtures. This study focuses on the categorization and examination of errors that occur due to omissions. The omissions referred to in this study are errors caused by the omission of “sentence components” and “sentence expressions” in students’ spoken sentences. The research results show that the former includes nouns, pronouns, verbs, adjectives, adverbs, auxiliary words, conjunctions, prepositions, numerals, quantifiers, and affixes, etc., while the latter mainly refers to punctuation, with a total of 12 situations. The study attributes these errors to the students’ proficiency in Chinese grammar, their capacity to adapt to spoken communication, and their shortcomings in comprehending and articulating specific topics. These errors can also be caused by other reasons such as performance anxiety, lack of experience with spoken Chinese, and insufficient understanding of the communication environment. According to the analysis provided, the study presents six instructional suggestions aimed at assisting students in overcoming these prevalent errors and enhancing their skills in spoken Chinese. This paper has significant consequences for comprehending the omissions made by Thai students in their spoken Chinese communication and for offering teachers useful guidance in teaching.